Electrospinning of marine-origin biopolymers toward tissue regeneration - Marques, A. L. P. (2017)
The aquatic environment, such as oceans, rivers, or lakes, is rich in biodiversity: fishes, marine sponges, jellyfishes, molluscs, crustaceans, or algae, among many others (including a huge and mostly unknown multiplicity of microorganisms). This variety turns out to be a gold mine in terms of natural biopolymers diversity. The exploitation of marine compounds for biological and biomedical applications is an area being explored more intensely in the latest years, in order to take advantage of all these abundant and underexplored marine resources. The idea is the valorization of underexplored marine organisms, such as seaweeds, or of by-products as consequence of the activity of fish processing industries. This involves, for instance, marine organisms that are caught by mistake on sea net fishes (by-catches) and are not used for food purpose, or fish processing by-products from industries. Indeed, ~75% of fish weight is discarded as processing 436leftovers such as skins, bones, fins, heads, guts, and scales, from which arises a huge potential for conversion into valuable products. Those natural polymers can be classified into proteins (collagen, gelatin, keratin, etc.), polysaccharides (agar, alginate, carrageenan, chitin, fucoidan, chondroitin sulfate, hyaluronic acid, etc.), and nucleic acids. Also bioceramics (hydroxyapatite, biosilica, calcium carbonates, etc.) take part in the constitution of some marine organisms (Ratner et al. 2004). Recent researches have arisen with the successful development of methods for isolation, purification, and characterization of these compounds from several marine sources, envisaging their application in many different industrial fields (Percival 1979; Nagai et al. 1999; Nagai and Suzuki 2000; Kinoshita-Toyoda et al. 2004; Abdou et al. 2008; Li et al. 2008).